5' flanking sequences of the rat tyrosine hydroxylase gene target accurate tissue-specific, developmental, and transsynaptic expression in transgenic mice - Banerjee, SA (J Neurosci, 1992)
Transgenic mice were generated in which sequences that flank the rat tyrosine hydroxylase (TH) gene were linked to the bacterial chloramphenicol acetyl transferase (CAT) gene. Mice bearing 4.8 kilobases (kb) of 5′ flanking DNA exhibited correct tissue-specific expression in the CNS and periphery. Expression was more robust in the CNS than in the periphery, although CAT activity was clearly detected in sympathetic ganglia (superior cervical ganglia) and the adrenal, the two peripheral tissues that contain TH-positive cells. Within the brain, CAT expression was seen in all the expected areas containing TH- positive cell bodies, with little or no expression in other regions. In the olfactory bulb, which contains the majority of the CNS TH cells, developmental expression of CAT was quantifiable and was found to parallel the postnatal rise in endogenous TH, with both TH and CAT reaching adult levels by postnatal day 21. Since TH activity in the olfactory bulb requires afferent input, the dependence of CAT activity on transsynaptic input was also assayed in transgenic mice. Like the endogenous TH activity, CAT levels were also reduced by deafferentation, in parallel with loss in endogenous dopamine levels. While previous experiments demonstrated that shorter 5′ flanking regions (2.5 kb and 3.5 kb of 5′ upstream sequences of the human and mouse TH gene, respectively) failed to direct accurate tissue-specific expression, our data demonstrate that 4.8 kb of 5′ flanking sequence of the rat TH gene contains sufficient regulatory information to mediate appropriate tissue-specific expression in all CNS and PNS tissues, as well as to mediate developmental and transsynaptic expression in the olfactory bulb.